2020
DOI: 10.1111/trf.15954
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of the PLASMIC score in patients with suspected thrombotic thrombocytopenic purpura: A systematic review and meta‐analysis

Abstract: Background The PLASMIC score was developed to identify patients with thrombotic microangiopathy who are most likely to have immune thrombotic thrombocytopenic purpura (TTP) and benefit from therapeutic plasma exchange (TPE). PLASMIC scores of 0‐4, 5, and 6‐7 are said to correspond to low, intermediate, and high probability of TTP, respectively. Study Design and Methods We conducted a systematic review and meta‐analysis on the diagnostic accuracy of the PLASMIC score in adults with suspected TTP. We evaluated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 24 publications
2
36
0
Order By: Relevance
“…Clinical scoring systems for assessing the probability of severe ADAMTS-13 deficiency in patients with suspected TTP PLASMIC score ≥5 has a sensitivity and specificity of 0.99 (0.91-1.0, 95% confidence interval [CI]) and 0.57 (0.41-0.72, 95% CI), respectively. 53 These results suggest that a patient with a PLASMIC and 20%), clinical judgement is required for reaching the final diagnosis, and other diagnoses should be considered as well (Figure 1). 17,57 In addition to plasma ADAMTS-13 activity and inhibitors, assessing ADAMTS-13 conformations via a monoclonal antibody binding assay may also aid the diagnosis and differential diagnosis of iTTP.…”
Section: Ta B L Ementioning
confidence: 92%
See 2 more Smart Citations
“…Clinical scoring systems for assessing the probability of severe ADAMTS-13 deficiency in patients with suspected TTP PLASMIC score ≥5 has a sensitivity and specificity of 0.99 (0.91-1.0, 95% confidence interval [CI]) and 0.57 (0.41-0.72, 95% CI), respectively. 53 These results suggest that a patient with a PLASMIC and 20%), clinical judgement is required for reaching the final diagnosis, and other diagnoses should be considered as well (Figure 1). 17,57 In addition to plasma ADAMTS-13 activity and inhibitors, assessing ADAMTS-13 conformations via a monoclonal antibody binding assay may also aid the diagnosis and differential diagnosis of iTTP.…”
Section: Ta B L Ementioning
confidence: 92%
“…Both scoring systems require ruling out the possibility of disseminated malignancy and the history of hematopoitic progenitor transplantation. Several other studies have independently validated the PLASMIC score 51‐54 . Paydary et al performed a meta analysis of 970 cases from 13 eligible studies published and demonstrated that a PLASMIC score ≥5 has a sensitivity and specificity of 0.99 (0.91–1.0, 95% confidence interval [CI]) and 0.57 (0.41–0.72, 95% CI), respectively 53 .…”
Section: Clinical Risk Assessment Scoresmentioning
confidence: 99%
See 1 more Smart Citation
“…This was confirmed in several subsequent studies, included in a recent meta-analysis 22 that defined a score of 5 points or more as the optimal cut-off, associated with the highest sensitivity and negative predictive values. In contrast, in the present study, a score of 4 or more was found to provide the best sensitivity, but the PLASMIC score still performed poorly.…”
Section: Discussionmentioning
confidence: 57%
“…Primary TMA is a medical emergency with high mortality and morbidity and, as such, requires astute recognition and prompt treatment. The PLASMIC score is a validated tool using easily testable blood markers to predict the likelihood of TTP [ 80 ]. In the absence of other explainable causes whilst awaiting ADAMTS13 results, a PLASMIC score >5 warrants urgent empirical treatment such as using plasma exchange and corticosteroids.…”
Section: Other Differential Diagnoses To Considermentioning
confidence: 99%